Teacher’s Strategies in Teaching English Speaking to Young Learners - Nia Florentina Robert; Widi Syahtia Pane (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
In teaching and learning process strategy is an activity that should be done both teacher and learner in order to get learning activity become effective and efficient. In short, teaching strategies are very important since they determine the success of teaching process. Strategies used by teachers should be interesting and can capture students’ attention. Some of the strategies used in teaching speaking are such cooperative activities as role-play, creative tasks, and drilling [1]. This article report a qualitative study that find out teacher’s strategies in teaching English speaking to young learners in junior school. Two junior school teacher in SMP Purnama were participated in this research and data were collected through interviews based on a case study design. The result of this study indicated the technique employed by the teacher in teaching speaking were so various such as role play, storytelling, social strategy and discussion. Teachers at SMP Purnama use more than one teaching strategy same like explanation above. This strategy helps students in an easier, faster, and more fun way mastering vocabulary so that it greatly supports the improvement of students' speaking skills. The teachers chooses a strategy based on the principles of teaching speaking. The teacher uses several strategies to help students are more motivated to learn and can add to their new vocabulary.